Antigenotoxic Effect of Curcumin and Carvacrol against Parathion Induced DNA Damage in Cultured Human Peripheral Blood Lymphocytes and Its Relation to GSTM1 and GSTT1 Polymorphism - Neeraj Kumar; Anita Yadav; Sachin Gulati; Kanupriya; Neeraj Aggarwal; Ranjan Gupta (Journal of Toxicology)
In recent years, the use of organophosphorus pesticides has been extensively increased and these compounds signify a major class of agricultural pesticides today. We studied antigenotoxic potential of curcumin and carvacrol against the parathion induced DNA damage in cultured peripheral blood lymphocytes using sister chromatid exchanges as a biomarker of genotoxicity. Heparinised fresh blood from healthy individuals was treated with 2.5 μg/mL concentration of parathion in presence of curcumin and carvacrol in order to observe the antigenotoxic potential of both curcumin and carvacrol. Significant reduction (P<0.05) was observed in the frequencies of SCEs in presence of 10 μg/mL and 15 μg/mL concentrations of curcumin as compared to parathion exposed sample. Similarly carvacrol had significant (P<0.05) antigenotoxic effect at the concentrations of 2.5 μg/mL and 5.0 μg/mL against the parathion. We also studied the effect of GSTT1 and GSTM1 on genotoxicity of parathion and antigenotoxic potential of curcumin and carvacrol. We did not observe any significant effect (P>0.05) of GSTT1 and GSTM1 polymorphism on genotoxicity of parathion and antigenotoxic potential of curcumin and carvacrol.